Up [videorecording (DVD)] - Docter, Pete; Peterson, Bob, 1961-; Asner, Edward; Plummer, Christopher; Nagai, Jordan; Lindo, Delroy, 1952-; Ranft, Jerome (Walt Disney Studios Home Entertainment ; Distributed by Buena Vista Home Entertainment, 2009)
Carl Fredericksen is a 78- year-old curmudgeon. He used to enjoy his modest life as a balloon seller when his adventure-loving wife Ellie was still alive. When she died, Carl was left with his memories and the awareness that they never made their dream journey to Paradise Falls in South America. When well-meaning officials consign Carl to Shady Oaks Retirement Home, he rigs thousands of helium balloons to his house and floats away. He discovers that Russell, a chubby Wilderness Explorer Scout has stowed away. In the tropical jungle, Carl and Russell find more than they bargained for. Charles Muntz is a crazed explorer whose newsreels once inspired Carl and Ellie; Kevin is an exotic bird with a weakness for chocolate; and Dug who is an endearingly golden retriever fitted with a voice box. More importantly, Carl and Russell discover they need each other.